Nacionalna kritična infrastruktura v Republiki Sloveniji - Prezelj, Iztok (Teorija in praksa, 2009)
The national critical infrastructure comprehends the most relevant socio-technical systems that support the stability of modern societies. These are energy, transport, telecommunication, information, financial, health and other systems. Their failures and related disturbances can escalate to threats to the stability and even security of contemporary societies. Many past terrorist activities deliberately focused on such infrastructures. The goal of this article is to diagnose the security relevance of critical infrastructure in general and identify the most critical infrastructural sectors in Slovenia. These sectors are structured mostly as complex and dispersed networks. The article also identifies some key threats and risks that contribute to the level of their criticalness as shown by the calculated index.
Keywords: Nacionalna varnost; National security; Infrastructure; Infrastruktura; Slovenia; Slovenija; tveganje; kritičnost